Analysis of occupation skills on all cause mortality in Pakistan - Ali, Muhammad Ghafoor; Husain, Saima Narjees (International Journal Of Community Medicine And Public Health, 2019)
Background: Occupational injuries/diseases are considered as leading problems for workers, especially in less developed countries. Based on International Standard Classification of Occupation (ISCO-08) four broad skill levels are defined. Employment has been established as a fundamental determinant of health and review of occupation/all cause mortality has been carried to observe the impact of occupation skill on cause of death. Methods: A retrograde study conducted on mortality data of State Life Insurance Corporation of Pakistan. Randomly 500 death cases were collected during study period between 2006 to 2018.The death claim instrument were proposal forms and death claim register. The data about occupation and cause of death was inserted on spread sheet of excel and finally analyzed through SPSS for occupation skill and cause of death. Results: Almost equal proportion of data found in skill-1 (14%) and skill-4 (12.6%) while maximum contribution found in skill level-2 (49.40%) followed by skill-3 (24%).The maximum percentages of mortality seen cause wise as CVS (49.39% skill-2), cancer (17.46% skill-4), road side accident (14.28% skill-1), multiple causes (6.67% skill-3), liver disorder (5.71% skill-1), CNS (3.17% skill-4), kidney disorder (5.71% skill-1), GIT (6.35% skill-4), respiration (3.17% skill-4), un-natural (2.02% skill-2), idiopathic (2.85% skill-1), endocrine (1.58% skill-4), body temperature (1.42% skill-1), poisoning (0.83% skill 3), electric shock (2.85% skill-1), sepsis (1.58% skill-4), obstetric (0.83% skill-3) and burn (1.42% skill-1) while lowest found as CVS(46.67% skill-3), cancer (7.14% skill-1), road accident (7.93% skill-4), multiple causes (2.85% skill-1), liver (1.58% skill-4), GIT (2.02% skill-2), respiration (1.61% skill-2) and idiopathic (0.40% skill-2). Many causes in skill-1 and skill-4 found no mortality. Conclusions: Mortality due to cardiovascular diseases found highest in all skills while lower frequency of death seen in other systematic disorders. Mostly highest and lowest mortality percentages found either in skill-1 or skill-4 whereas comparatively higher percentages have steadily been maintained in skill-2 and skill-3.